Models to Find Influential Users for Viral Marketing in Multilayer Networks - Rao, Katakamsetty Venkatakrishna (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Models to Find; Influential Users for; Viral Marketing; in Multilayer Networks